VALUATION ANALYSIS TO DETERMINE BUSINESS EXPANSION OF PT MERDEKA - Kevin Japri, Leonardo
PT Merdeka is an IT consultant and development company located in Depok. PT Merdeka was established in 2014 under Perseroan Komanditer (CV) business entity, but due to the business they do which mainly involve public company, PT Merdeka business entity was restructured in 2016 into Perseroan Terbatas (PT) business entity. In February 2018, PT Merdeka has been invested by 2 of PT Infrastruktur’s board of directors. And currently, PT Inovasi as a subsidiary under PT Kapital and still in the same circle as PT Infrastruktur, has also seeking to be PT Merdeka’s investor and shareholder. PT Inovasi is looking for 15% shares in total, the same amount as PT Infrastruktur has, in return they offer a bigger networking into PT Kapital and funding for PT Merdeka’s expansion plan in 1 year ahead. The valuation analysis is conducted to determine fair value of PT Merdeka which finally become the basis to determine projected potential growth and gain of PT Merdeka’s business expansion. Furthermore, the valuation analysis will be executed by using asset-based approach which proposed by PT Inovasi, and Discounted Cash Flow (DCF) model & multiple approach which proposed by PT Merdeka. Based on the proposed valuation method, the alternative solutions were formulated into three alternatives: (1) Reject this financial activity and let the company grow by their own. (2) Accept the offer by asset-based approach with share purchase from the founders’ shares. (3) Accept the offer by DCF model or multiple approach with new injection in venture capital and issuance of new shares. However, there still are many other considerations besides fair value and potential gain, such as the easiness to set the deal, bargaining power of PT Merdeka, direct or indirect gain to the founders, etc. In the end, the final decision still depends on founders’ perspective supported by all the analysis in this research. Summarizing from the valuation analysis to determine business expansion, the recommendation for PT Merdeka is to take PT Inovasi’s investment by using asset-based approach. Even though the potential gain for the founders isn’t the highest, but considering the easiness to set the deal from both parties due to direct cash to the founders, highest potential gain to PT Inovasi, third highest potential gain to PT Inovasi + PT Infrastruktur, low investment cost from PT Inovasi, and has a growth potential.